(untitled) (Scientific journal of the Fergana State University, 2024)
The article reflects on the fate of a woman, which is illuminated in the story of the German artist Stevan Zweig. How cruel is human fate, sometimes joyful, sometimes dangerous, that a person is capable of giving up his interests and sacrificing himself, that the human heart is vulnerable, thirsts for love, that any courage, heroism, sometimes even a crime can cause a flow of strong emotions in a person, especially internal experiences women, her psyche and her courage, patience, giving her life for the sake of a child. In fiction, human suffering and feelings are expressed through words. Knowing how to use this word skillfully depends on the artistʼs style. In the story “Letter from a Stranger Woman,” Stevan Zweig skillfully describes the psychology of a woman who falls in love with a writer and is ready to do anything for the sake of the creative self, the image of a woman reflecting this self, based on the epistolary genre. The article explains that after the death of her child, a strange woman, having renounced her will and honor, informs the father of her child through a letter that the boy who left this world before she knew him is her child. He clearly feels the divine feelings of love, devotion, fidelity between a woman and a man, and the unrequited love of a stranger for life, her patience, the strong will of a woman, her endless love for her beloved wife and child.​